2012
DOI: 10.1007/s12576-012-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic survival and constitutively active autophagy in self-beating atypically-shaped cardiomyocytes (ACMs): characterization of a new subpopulation of heart cells

Abstract: Atypically-shaped cardiomyocytes (ACMs) are a new subpopulation of spontaneously beating heart cells with a peculiar morphology identified within a culture of cardiac myocyte-depleted fraction (CMDF) cells obtained from adult mouse heart. ACMs originate from small cells in CMDF and grow in size and start beating within ~3 days culture without appreciable proliferation or express stem cell marker proteins, but stay in the heart until elderly stages. However, the characteristics of ACMs are largely unclear. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…1c). No viable ventricular myocytes were detected, even in independent cultures, over these 6 days of culture14. Instead, fibroblast-like cells originating from the endogenous heart tissue, such as cardiac fibroblasts or dedifferentiated cardiomyocytes2122, proliferated, becoming nearly confluent after culture for 20 days (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1c). No viable ventricular myocytes were detected, even in independent cultures, over these 6 days of culture14. Instead, fibroblast-like cells originating from the endogenous heart tissue, such as cardiac fibroblasts or dedifferentiated cardiomyocytes2122, proliferated, becoming nearly confluent after culture for 20 days (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Atypically-shaped cardiomyocytes (ACMs) are a type of cardiac progenitors identified in the cultures of cardiomyocyte-removed fraction obtained from mouse cardiac ventricles that spontaneously develop into beating cells within 3–5 days culture121314. Beating ACMs possess a peculiar morphology far different from a typical cardiomyocytes and the electrophysiological properties similar to those of sino-atrial (SA) nodal pace maker cells12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent report described a population of heart cells with a morphology that differs from cardiomyocytes (hence the name "atypically-shaped cardiomyocytes (ACMs)"). These cells are particularly resistant to ischemic conditions and spontaneously develop into beating cardiomyocytes, suggesting the existence of residual fetal heart cells in the adult murine heart [82]. Non-the-less, the regenerative potential of the adult mammalian heart is extremely limited.…”
Section: General Aspects About Autophagy and Cardiac Regenerationmentioning
confidence: 99%
“…Likewise, inducing autophagy in bone marrow-derived mesenchymal stem cells has been proposed as an approach to increase their viability upon transplantation, and hence their therapeutic efficiency in infarcted hearts [95,96]. Interestingly, the ACMs described by Omatsu et al were also reported to have numerous autophagosomes, and their ability to develop in vitro was shown to be sensitive to pharmacological inhibition of autophagy [82]. Furthermore, autophagy has been shown to be required for both the maintenance of stem cell pools in several tissues [89,[97][98][99].…”
Section: Therapeutic Potential Of Autophagy Upon Myocardial Infarctionmentioning
confidence: 99%